ITO/ATO/TiO2 triple-layered transparent conducting substrates for dye-sensitized solar cells - Yoo, Beomjin; Kim, Kyungkon; Lee, Seung Hoon; Kim, Won Mok; Park, Nam-Gyu (ELSEVIER SCIENCE BV, 2008)
A novel transparent conductive oxide film based on the triple-layered indium tin oxide (ITO)/antimony-doped tin oxide (ATO)/titanium oxide (TiO2) has been developed for dye-sensitized solar cells by using radio frequency magnetron sputtering technique. Effects of the absence and presence of TiO2 layer and the ITO layer thickness were investigated. Deposition of ATO layer was found to stabilize the thermal instability of ITO. Little change in sheet resistance and optical transmittance was observed by introduction of insulating thin TiO2 layer on top of the ATO layer, whereas photovoltaic performance was significantly influenced. The conversion efficiency was improved from 4.57% without TiO2 layer to 6.29% with TiO2 layer. The enhanced photovoltaic performance with addition of TiO2 layer was attributed mainly to the improved adhesion and partially to the reduced electron loss at the ITO/ATO conductive layer. Increase in the ITO layer thickness resulted in a slight decrease in photocurrent due to the reduced optical transmittance. When compared with the conventional fluorine-doped tin oxide (FTO), the ITO/ATO/TiO2 conductive material exhibited similar photocurrent density but higher photovoltage and fill factor, resulting in better conversion efficiency. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: CONVERSION EFFICIENCY; ELECTRICAL-IMPEDANCE; TIO2 FILMS; CIRCUIT